KEBEBASAN BERAGAMA DALAM MASYARAKAT (Studi Tentang Pindah Agama dan Konsekuensinya Menurut Pemikir Muslim Kontemporer) - Basuki, A. Singgih (Religi: Jurnal Studi Agama-agama, 2013)
God has given human beings tremendous grace of freedom in con- ducting their life. Because of their freedom’s nature, human beings are not under pressure to do something at all cost. Thus, to embrace Islam is not a type of pressure to humans. The central issue is whether Mus- lim who converts into the other religion is free by preference or bound to Laws and punishments. The research focuses on the Islamic con- temporar y thought of  both ulama’s (Islamic scholar) majority and Maulana Muhammad Ali. The research shows that the majority of Ulama claims Muslim who converts to other religions should be urged to engage in taubah (repentance and back to Islam) before the death penalty. On the contrary, Maulana Muhammad Ali argues that they are freed from the worldly punishment. The latter also states that they get a kind of punishment if they both rebel and declare war to Islam.In Islam, the religious freedom –it is not always apply the term al- hurriyah —has affiliated to the core of Islamic thought in accordance with the dynamics of time, however the term al-ikhtiyar is obviously identical to the freedom. For instance, the freedom and human rights (HAM) terms are both identical but they bear different meanings. In human rights aspect, the freedom ranges its multidimensional ele- ment into religious freedom as well. The phenomenon of Murtad (apostasy) then becomes the threat to the Islamic community. Murtad is harmful leading to the change of  muruah in a Muslim country. In this context, it is reasonable for Abu Bakar As-Siddiq to declare a firm enforcement in order to maintain the stability to fight against the waves of murtad during his reign.Thus Muslims are prohibited to alter their religions since Islam is a perfect and compatible belief to the concept of human creation. When choosing to become a Muslim, one has confessed in the names of God and the Messenger to obey all Islamic teachings including the prohibition to denounce Islam. If Muslims confess to leave Is- lam, they then basically betray and break their promises to God. The research uses literary and documentary methods in discussing a con- version-related issue and studying conversion cases in the society. The finding of the research contributes to some references and con- siderations for both the Islamic leaders and Muslim scholars.